Découpage territorial et décentralisation : un réservoir des problèmes socio- politiques et juridiques dans les nouvelles provinces en République Démocratique du Congo - LIFOLI BALEA, Jean-Pierre (IJRDO - Journal of Social Science and Humanities Research, 2018)
To bring closer the administration of managed them and for the necessities of development, the Democratic Republic of Congo opted for decentralization, as fashion of management of the country. This decentralization is accompanied by the territorial carving. Since 2015, the number of the provinces of the country passed from eleven to twenty-six. Although the territorial carving and decentralization present a lot of advantages, they also present a lot of risks for a multicultural country and multi - ethnic as the RDC. Among these risks, we can mention racism, xenophobia, the ethno-political conflicts… All these factors constitute sources of dissension, instability and weakening of the provinces newly created. To lessen this danger, it is necessary that the original and the non original of all provinces of the country speak themselves as brothers and solve what divides them peacefully. To this level, the intervention of the state and the observance of the laws of republic that allow to all Congolese to get settled everywhere in his/her/its country are very indispensable.